Tourism Activity Development Model in Increasing Visitors in Sapari Tourism Village, East Kalimantan - Said, Farid; Widjaja, Herry Rachmat; Trinanda, Alvira (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims: (1) to identify the current form of tourism activities in Sapari Tourism Village, Tana Tidung Regency, North Kalimantan (2) To create tourism activity development in increasing visitors in Sapari Tourism Village, Tana Tidung Regency, North Kalimantan. This study uses a qualitative approach with the type of research and development (RnD) with the Sugiyono development model. The types of data used are primary data and secondary data by producing products that are validated by academic experts related to tourism packages. The results of the study indicate that one of the efforts to develop tourism activities is to create tourism package products that are expected to be able to attract visitors to come to Sapari Tourism Village by seeing that the direction of a tour is through the tour package. With this tour package, tourism activities can reach more market segments and influence visitor interest. The contribution of this research can provide simple knowledge in making tour packages that will mobilize local resources and generate added value for the community.